A novel model of the cross-section variation effect induced by contraction convection on freckle defects in directional solidification - Yang Liu; Yan Shang; Fu Wang; Dexin Ma; Qiang Yang; Xiaorui Chen; Jiantao Wu (Journal of Materials Research and Technology)
A Ra model to simulate the freckle tendency in directional solidification of single-crystal superalloy containing the geometrical effects was introduced. The CSVE (cross-section variation effect) mechanism of freckle formation in the directional solidification process of Ni-based superalloys was discussed in detail. The possible shrinkage convection related to the macro segregation equation can strengthen the interdendritic convection and result in more severe freckle formation. Two approaches for explaining CSVE were discussed in the article, accompanied by experiments and computations. The existing Ra simulations that include geometrical effects support the proposition that shrinkage convection may be the primary contributing factor to CSVE. After considering CSVE, the positional accuracy in freckle prediction has been improved, and the reasons for this improvement have been further explored. These studies contribute to the construction of a cost-effective method for quickly estimating the distribution of freckle defects.